DESIGN AND DEVELOPMENT OF ENGLISH LISTENING EXERCISE VIDEOS USING VOICE DUBBING TECHNIQUES - Jimmy Pratama; Jacky Christhomas (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Video is one of the developments in information technology that has a function as an introduction to information conveyed through audio-visual media. Ease of playing back videos, making videos as a medium that can improve and develop the ability to understand information presented in a structured manner such as learning English through video. One of the international communication standards is the ability to communicate in English. English language skills also play an important role in employment in the modern era like today. With research on developing English listening practice videos using voice dubbing techniques, this video can provide audiences with learning and practice about English. The method used for the development of this video is the MDLC method. The results of this study are expected to improve the audience's ability to speak English.